2021
DOI: 10.3389/fcimb.2020.593805
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Fission Regulator DRP1 Controls Post-Transcriptional Regulation of TNF-α

Abstract: The mitochondrial network plays a critical role in the regulation of innate immune signaling and subsequent production of proinflammatory cytokines such as IFN-β and IL-1β. Dynamin-related protein 1 (DRP1) promotes mitochondrial fission and quality control to maintain cellular homeostasis during infection. However, mechanisms by which DRP1 and mitochondrial dynamics control innate immune signaling and the proinflammatory response are incompletely understood. Here we show that macrophage DRP1 is a positive regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 86 publications
5
18
1
Order By: Relevance
“…Though several studies have suggested DRP1 induces in ammatory signaling, here we show a link between DRP1 and suppression of HDM-induced proin ammatory cytokine and chemokine release by airway epithelia in culture. In agreement with our work, another study demonstrated DRP1 suppresses pro-in ammatory signaling in macrophages stimulated with LPS via regulation of release of mitochondrial damage-associated molecular patterns (DAMPs) (53).…”
Section: Discussionsupporting
confidence: 91%
“…Though several studies have suggested DRP1 induces in ammatory signaling, here we show a link between DRP1 and suppression of HDM-induced proin ammatory cytokine and chemokine release by airway epithelia in culture. In agreement with our work, another study demonstrated DRP1 suppresses pro-in ammatory signaling in macrophages stimulated with LPS via regulation of release of mitochondrial damage-associated molecular patterns (DAMPs) (53).…”
Section: Discussionsupporting
confidence: 91%
“…Though several studies have suggested DRP1 induces inflammatory signaling, here we show a link between DRP1 and suppression of HDM-induced pro-inflammatory cytokine and chemokine release by airway epithelia in culture. In agreement with our work, another study demonstrated DRP1 suppresses pro-inflammatory signaling in macrophages stimulated with LPS via regulation of release of mitochondrial damage-associated molecular patterns (DAMPs) [ 33 ]. Mitochondrial DAMPs play an important role in inflammatory signaling in response to lung injury [ 53 , 54 , 55 ].…”
Section: Discussionsupporting
confidence: 90%
“…One of the components of bacterial origin is lipopolysaccharide (LPS). LPS is known to induce DRP1 activation [ 32 , 33 , 34 ]. Therefore, we treated HBECs with LPS (0.6 ng/mL) at a level comparable to that found in the HDM used in our studies, as well as at a higher dose (100 ng/mL), to examine whether LPS alone is responsible for the DPR1 response induced by HDM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, fission occurs through the inhibition of mitochondrial fusion protein. Second, the fission process demands the presence of mitochondrial fission, such as dynamin-related protein 1 (DRP1) [59], which interacts with human fission factor (Fis 1) and mitochondria fission factor (MFF). Thus, the extensive activation of DRP1 may increase mitochondrial fragmentation, increasing reactive oxygen species followed by decreased ATP production [60,61].…”
Section: Diaphragm Dysfunction and Copdmentioning
confidence: 99%